Effects of Aromatic Hydrocarbons and Marine Water from Niger Delta on the β-Galactosidase Activity of Mutant Escherichia coli - , Bright Obidinma Uba (Archives of Current Research International, 2019)
Aims: To determine effects of aromatic hydrocarbons and marine water from Niger Delta on the β-Galactosidase activity mutant Escherichia coli. Study Design: Fifteen treatments and the control designs were set up in triplicates in microtitre plates containing 200 µL of the 100% concentration of samples (three marine waters and distilled water spiked each with xylene, anthracene and pyrene). The fifteen treatments and control (HgCl2) set ups designated as A, B, C, D, E, F and G were used to determine their median effective concentration (EC50) for the inhibition of β-Galactosidase activity of mutant Escherichia coli. Place and Duration of Study: Department of Microbiology, Chukwuemeka Odumegwu Ojukwu University, Uli Nigeria between February, 2017 to July, 2017. Methodology: A laboratory scale study was carried on the water samples from the three studied areas using physicochemical analyses and bacterial Toxi-chromo test. Results: The findings revealed that the three sampling sites contain higher quantities of aromatic hydrocarbons, heavy metals and other physico-chemical parameters in the sediment samples than water samples. Xylene distilled water had the highest EC50 of 3.417 ± 0.094 mg/l while pyrene Onne water had the least EC50 of 0.015 ± 0.002 mg /L. Also, pyrene and anthracene are significantly (P = .05) highly toxic aromatic hydrocarbons (EC50 < 1 mg /L) while xylene is a significantly (P = .05) toxic aromatic hydrocarbon (1 mg /L < EC50 ≤ 10 mg /L) compare to the positive control (HgCl2) (EC50 < 1 mg /L) indicating that enzyme inhibition among test samples were much different from the positive control. Conclusion: Thus, the toxicity results (< 0.1 mg /L < EC50 ≤ 10 mg /L) in this study indicate that the potential eco-toxicity and environmental health effects of these toxicants should be given attention in order to get rid of their dangerous outcomes.